PENERAPAN METODE THINK TALK WRITE UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI DAN HASIL BELAJAR TEMA DAERAH TEMPAT TINGGALKU SISWA KELAS 4 SDN TEGALREJO 01 - Septiani, Amalia; Wahyudi, Wahyudi; Indarini, Endang (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract This research aims to improve communication skills and student learning outcomes based on the some steps Think Talk Write method. The research used is Classroom Action Research (CAR) in two cycles. Each cycle consists of three taap, namely planning, implementation and observation and reflection. The subject of this research is 4 grade in SDN Tegalrejo 01amounted to 27 students. The result show that that there was an increasing communication ability is seen from the average classically, at pre cycle stage is 53,8 with low criterion. The first cycle increased to 78.8 with medium criteria and cycle II increased to 88.7 with high criteria.Completeness of learning result of theme of 8 Indonesian content, IPS, PPKn at pre cycle stage equal to 67,24 with 63% completeness percentage, cycle I equal to 76,77 with percentage 67%, in cycle II equal to 82,20 with percentage 92%. Thus the standard Think Talk Write method can improve communication skills and student learning outcomes Keywords: Think Talk Write Method, communication skills and student learning outcomes Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan komunikasi dan hasil belajar siswa berdasarkan langkah ? langkah metode Think Talk Write. Penelitian yang digunakan adalah Peneltitian Tindakan Kelas (PTK) dalam dua siklus. Tiap siklus terdiri dari tiga tahap, yaitu perencanaan, pelaksanaan dan observasi serta refleksi. Subjek penelitian ini adalah kelas 4 di SDNTegalrejo 01 berjumlah 27 siswa. Hasil penelitian menunjukkan peningkatan kemampuan komunikasi dilihat dari rata ? rata secara klasikal, pada tahap pra siklus adalah 53,8 dengan kriteria rendah. Siklus I meningkat menjadi 78,8 dengan kriteria sedang dan siklus II meningkat menjadi 88,7 dengan kriteria tinggi. Ketuntasan hasil belajar tema 8 muatan Bahasa Indonesia, IPS, PPKn pada tahap pra siklus sebesar 67,24 dengan presentase ketuntasan 63%, siklus I sebesar 76,77 dengan presentase 67%, pada siklus II sebesar 82,20 dengan presentase 92%. Jadi metode Think Talk Write yang disesuaikan standar proses dapat meningkatkan kemampuan komunikasi dan hasil belajar siswa Kata Kunci : Metode Think Talk Write, kemampuan komunikasi dan hasil belajar siswa